The existence and role of traditional cultural beliefs in conserving Sibaganding Tua sacred forest. Issue 3 (June 2021) - Sinambela, S N; Badaruddin,; Slamet, B
Abstract: The conversion of religion has made the existence of several cultural values changed and lost their practice in the community of Sihotang Village. The purpose of this research is to analyze the relationship between the existention of Sibaganding Tua sacred forest with the beliefs and customs of the people of Sihotang Village. This research using qualitative research method by In-depth interview with the community. The results show that the concept of sacred forest does not contradict to the teachings of Christianity so that the practice of customary rules, taboos and beliefs related to sacred forests is still ongoing. People also get benefit from this forest, which is the main source of their water needs. There is a relationship between beliefs and customs with the existention of the forest is found. Communities increasingly protecting the forest and obey the law when there are ecological benefits received. This will increase the protection of the sacred forest. Meanwhile, education and modernization of house building have eliminated the ritual practice of the tree using rules for Borotan and Bungkulan of Batak house from sacred forests. However, it has indirectly provided protection and reduced tree logging activities in Sibaganding Tua sacred forest.